2022
DOI: 10.52609/jmlph.v2i1.33
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the systematic review of post COVID-19 syndrome

Abstract: Background: The declaration of the COVID-19 pandemic triggered a global inquiry into the transmission, mortality, risk factors, and management of the disease. Recently, however, attention has shifted toward its long-term consequences. There is a need for a better understanding of the predictors and symptoms of post-COVID syndrome, to ensure appropriate care for patients recovering from COVID-19 beyond the acute phase. Methods: We searched PubMed, Google Scholar, Cochrane databases, and available data in the PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
0
0
1
Order By: Relevance
“…The authors concluded that persistent symptoms, isolation feelings, fear and stigma, emotional distress, a fatalistic attitude, and return to life were the key aspects of participants' experience after hospital discharge. Alhumayn et al [26] stated that given the impossibility to correlate acute symptoms with the onset of chronic sequelae and the PCS manifestation variability, a multidisciplinary team is mandatory to depict each patient's needs. Sanchez-Sanchez-Ramirez et al [64], in a systematic review of the literature and meta-analysis, intended to explore post-COVID-19 effects on patients' chest computed tomography, lung function, respiratory symptoms, fatigue, functional capacity, HRQoL, and the ability to return to work after three months post-infection through the analysis of 24 papers that presented information on a total of 5323 adults, with a prevalence of fatigue of 38%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that persistent symptoms, isolation feelings, fear and stigma, emotional distress, a fatalistic attitude, and return to life were the key aspects of participants' experience after hospital discharge. Alhumayn et al [26] stated that given the impossibility to correlate acute symptoms with the onset of chronic sequelae and the PCS manifestation variability, a multidisciplinary team is mandatory to depict each patient's needs. Sanchez-Sanchez-Ramirez et al [64], in a systematic review of the literature and meta-analysis, intended to explore post-COVID-19 effects on patients' chest computed tomography, lung function, respiratory symptoms, fatigue, functional capacity, HRQoL, and the ability to return to work after three months post-infection through the analysis of 24 papers that presented information on a total of 5323 adults, with a prevalence of fatigue of 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate or severe fatigue was reported more frequently in female subjects, and no marked difference through ethnicity or body mass index (BMI) was noticed [15]. Alhumayn et al [26], in a relevant systematic review of systematic reviews, pointed out that fatigue might result from many factors, including respiratory muscle weakness, post-viral fatigue syndromes, and possible general deconditioning. The authors also defined how fatigue significantly impacts the health-related quality of life (HRQoL) and general health status of post-COVID-19 subjects, with a decrease in up to 69% of patients from 14 days to 3 months post infection and a reduction in the performance of activities of daily living (ADL) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Описательные исследования во время первой волны пандемии в 2020 г. показали, что не менее 10-20% субъектов не полностью выздоровели через три недели [4,5]. Сог ласно опросу, проведенному Управлением национальной ста тистики Великобритании (ONS) в 2021 г., у 65% лиц, перенесших COVID-19, симптомы длились более 12 нед.…”
Section: Introductionunclassified